Analysis of the regenerative capacity of human serum exosomes after a simple multistep separation from lipoproteins. (23rd November 2020) - de Boer, Candice; Calder, Bridget; Blackhurst, Dee; Marais, David; Blackburn, Jonathan; Steinmaurer, Martina; Woudberg, Nicholas J.; Lecour, Sandrine; Lovett, Jason; Myburgh, Kathy; Bezuidenhout, Deon; Human, Paul; et al.
Abstract: Due to the abundance of lipoproteins in blood, it is challenging to characterize the biological functions and components of blood‐derived extracellular vesicles. The aim of this study was to develop a multiple‐step purification protocol to separate serum exosomes from serum proteins and lipoproteins and assess their regenerative potential. Exosomes were isolated by concentrating them in human serum using ultracentrifugation (UC), followed sequentially by density gradient (DG) UC and size exclusion chromatography (SEC). Purity and characterization were assessed by western blots, Lipoprint®, enzyme‐linked immunosorbent assay, electron microscopy, mass spectrometry, and nanoparticle tracking analysis. Functionality was assessed by cell proliferation analysis and with an in vivo subcutaneous angiogenesis model. SEC alone isolated nano‐sized vesicles possessing vesicle markers TSG101 and CD9, but there was a substantial presence of apolipoprotein B, predominantly derived from very‐low‐ and intermediate‐density lipoprotein particles. This was reduced to an undetectable level using the combined UC DG SEC approach. Mass spectrometry identified 224 proteins in UC DG SEC isolates relative to the 135 from SEC, with considerable increases in exosome‐related proteins and reductions in lipoproteins. A consistent but limited increase in human dermal fibroblast proliferation and evidence of neovascularization enhancement were observed after exposure to UC DG SEC exosomes. An UC DG SEC purification protocol considerably improved the removal of lipoproteins during isolation of serum exosomes. The purified exosomes stimulated cell proliferation and potentially increased an in vivo angiogenic response. This multistep purification allows for more accurate identification of serum exosome functional activity and composition.